Strategic change management in the public sector : an EFMD European case book - Longo, Francesco; Cristofoli, Daniela (Chichester, West Sussex, England ; Hoboken, N.J. : John Wiley & Sons, 2007)
The ability to manage change-management processes depends on individual skills and organisational culture. These skills have to be increased and practiced; in this perspective, the reading and analysis of this casebook can generate mental training about innovation. In order to look for common problems and solutions for implementing managerial development, a rich portfolio of European cases, with at least one representative for every European component, is presented. Typically comparative works select different countries according to criteria such as English speaking, countries from the same re.
Managing public reforms effectively: a strategic change management approach / Francesco Longo -- A guide through the case-book / Daniela Cristofoli and Francesco Longo -- The brussels port authority's container terminal: the ups and downs of public-private partnerships / Jan Mattijs -- Managerial changes at Estonian hospitals / Ruth Sepper and Ruth Alas -- Lolf and changes in the French public sector: the case of the Paul Cezanne University -- Aix-Marseille III / Robert Fouchet and Emil Turc -- Political and managerial change in the city of Coesfeld / Harald Plamper and Ingrid Beutel-Menzel -- Implementing equal in Megara municipality / Joyce Liddle and Ioannis Oikonomopoulos -- Change management process in the city of Amersfoort / Piet Severijnen and Job van de Bovenkamp Ba -- Milan municipality and the governance of municipal enterprises / Daniela Cristofoli and Francesco Longo -- Managing Barcelona's olympic heritage / Lidia Garcia [and others] -- Management by results: its way from idea to dogma in the case of Sweden / Goran Sundstrom -- Municipality of Baar: Speyer award for local governance / Albert Hofmeister and Jurg Dubendorfer -- The integration of performance management into the management of the London Borough of Lewisham / Paul Joyce.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Public administration -- Europe -- Case studies; Organizational change -- Europe -- Case studies; Strategic planning -- Europe -- Case studies; Public institutions -- Europe -- Management -- Case studies; Administrative agencies -- Europe -- Management -- Case studies; Administration publique (Science) -- Europe; Changement organisationnel -- Europe; z; z; Administration publique -- Europe -- Gestion; POLITICAL SCIENCE -- Public Affairs & Administration; Administrative agencies -- Management; Organizational change; Public administration; Public institutions -- Management; Strategic planning; Europe; Strategisches Management; Internationaler Vergleich; Verwaltung; Europa; Case studies